1999
DOI: 10.1152/ajprenal.1999.277.1.f105
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PDGF in pressure-induced mesangial cell proliferation through PKC and tyrosine kinase pathways

Abstract: In glomerular hypertension, mesangial cells (MC) are subjected to at least two physical forces: mechanical stretch and high transmural pressure. Increased transmural pressure, as well as mechanical stretch, promotes MC proliferation, which may enhance glomerulosclerosis. The exact mechanism of this effect is not fully understood. We examined the effects of transmural pressure alone on cell proliferation and DNA synthesis and investigated the role of platelet-derived growth factor (PDGF) and basic fibroblast gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In skeletal muscle cells and osteoblast-like cells, mechanical stretch increased FGF-2 expression (7,35), but other models that generate mechanical stretch did not find an effect on FGF-2 expression in the heart, in skeletal muscle, or in mesangial cells (14,30,55). Our results are the first to demonstrate that mechanical stretch increases the expression of FGF-2 mRNA in vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 37%
“…In skeletal muscle cells and osteoblast-like cells, mechanical stretch increased FGF-2 expression (7,35), but other models that generate mechanical stretch did not find an effect on FGF-2 expression in the heart, in skeletal muscle, or in mesangial cells (14,30,55). Our results are the first to demonstrate that mechanical stretch increases the expression of FGF-2 mRNA in vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 37%
“…Slight changes of osmolarity entailed enhanced PLA 2 enzymatic activity (53), and direct mechanical stimulation of skeletal muscle cells potentiated PLA 2 but not PLC activity (94). On the contrary, PLC could be mechanically activated in mesangial cells (46). Especially in blood vessels, mechanical activation of PLC was observed (43,60,70,78).…”
Section: Potential Mechanosensors Discussed So Farmentioning
confidence: 99%
“…A recent study has shown that transmural pressure applied to the cells enhanced MC proliferation through activation of mitogen-activated protein kinases [5]. Quite recently, we have demonstrated that transmural pressure resulted in a pressure level dependent increase in DNA synthesis and cell proliferation through activation of protein kinase C and tyrosine kinases [6]. This study revealed that the maximal increase in DNA synthesis and cell proliferation occurred at a pressure level of 80 mm Hg which was almost identical to that transmitted to the glomerular capillary wall of five-sixths renal ablation rats, a model of advanced renal failure [7].…”
Section: Introductionmentioning
confidence: 99%